Олесь Гончар: мить і вічність - Галич, В.М. (Інститут літератури ім. Т.Г. Шевченка НАН України, 2009)
В данной статье подан проблемно-тематический анализ публицистики Олеся Гончара, обращено внимание на особенности ее жанровой системы и поэтики. In this article problematical and topical analysis of Oles Gonchar’s publicistic works is represented, the author emphasizes on the particularities of genre system and poetical features of these works.